SOIL-TRANSMITTED HELMINTH INFECTION AND EOSINOPHIL LEVELS AMONG WASTE COLLECTORS IN BANDA ACEH - Imansyah Putra, Teuku Romi; Loesnihari, Ricke; Panggabean, Merina (Institute of Topical Disease Universitas Airlangga, 2018)
Soil-Transmitted Helminth (STH) has infected more than one billion people worldwide. Waste collectors are at risk for STH infection because their work mostly in contact with soil and waste. Eosinophilia is a sign of human immune response to STH infection in addition to increased IgE and cytokine production. This cross sectional study aims to examine the association between STH infection and eosinophil levels among waste collectors in Banda Aceh. The study sample were 60 waste collectors working for the Sanitation department of Banda Aceh. Examination of stool samples using Kato-Katz technique revealed the prevalence of STH infection among waste collectors was 23.3% (14/60), consisting of T.trichiura infection (21.7%) and mixed infection (1.6%). There were no single infections of A. lumbricoides nor the hookworm infection was found. Blood tests to count eosinophil showed the prevalence of eosinophilia at 21.7%. There was no significant correlation between the intensity of STH infection and eosinophil levels (p value = 1.00). This study does not recommend the use of eosinophilia to indicate STH infection.